Islamic Political Thought And Its Implementation In The Contemporary World - Ilhamni Ilhamni; Meirison Meirison; Zerly Nazar (Islamadina : Jurnal Pemikiran Islam, 2022)
Legitimate politics in contemporary studies is a name for the rulings and behaviors by which the nation's affairs are managed in its government, Legislation, and judiciary. And all its executive and administrative authorities, and in its external relations that link it to other nations in a state of peace and war, international relations and international law, and its vocabulary in international treaties, political and diplomatic relations, and international humanitarian law, concerning the influence of Islamic jurisprudence. Legitimate politics is one of the tremendous methodological sciences in Islamic heritage. It is a tool in the hands of the rulers in the state to lead the nation and achieve its religious and worldly interests. Considering the people's behavior and situations, consider the developments entering individual lives and countries under the Sharia provisions and realizing its purposes. We conducted a literature study in discussion with a descriptive analysis approach. We analyze the concept of Islamic politics and its implications for government policy and compare contemporary times. We get the scope of Islamic political movement only in family law. We can still be developed in Islamic economics, which significantly benefits Muslims in various countries. Islamic economics has a broad scope that does not directly collide with the policies in multiple countries. Regulations on the political continuity of shariah development in various fields can be placed in the constitutions and rules in numerous countries. Other Islamic laws cannot be applied yet due to circumstances that force Muslims to be under the power and influence of very strong non-Muslims.